Galectin-3 increase in endurance athletes. (29th August 2020) - Hättasch, Robert; Spethmann, Sebastian; de Boer, Rudolf A; Ruifrok, Willem PT; Schattke, Sebastian; Wagner, Moritz; Schroeckh, Sabrina; Durmus, Tahir; Schimke, Ingolf; Sanad, Wasiem; Baumann, Gert; Borges, Adrian C; et al.
Abstract: Background: Galectin-3 is a new and promising biomarker for heart failure and myocardial fibrosis. Although endurance exercise is a crucial element in cardiovascular disease prevention, the relationship between exercise and plasma levels of galectin-3 is still unknown. To date, the relationship between regular exercise and myocardial fibrosis is not fully understood. This study investigates the relationship between endurance exercise and plasma levels of galectin-3. Methods: Twenty-one male, healthy non-elite marathon runners were examined before and within 1 hour after a strenuous run of 30 km after 4-day training abstinence. Examination included blood samples for galectin-3, echocardiography, and cardiac magnetic resonance imaging (CMR). In addition, to distinguish between cardiac or skeletal muscular origin of galectin-3, 27 C57Bl/6 J mice performing voluntary wheel running and 25 sedentary mice were analysed. Results: Plasma galectin-3 in endurance athletes increased from baseline to post exercise (12.8 ± 3.4 ng/ml to 19.9 ± 3.9 ng/ml, p < 0.001) while the systolic left and right ventricular function remained unchanged. Interestingly, baseline plasma levels of galectin-3 were in normal range but higher than in healthy sedentary controls. However, in CMR there was no correlation between baseline galectin-3 levels and the detection of myocardial fibrosis. In animal studies, the relative level of mRNA for galectin-3 in active mice was significantly higher compared to sedentary mice. This increase was most pronounced in skeletal muscle (98.0% higher, p < 0.001) and not in the myocardium of the left ventricle (19.9% higher, p = 0.043). Conclusions: Plasma galectin-3 is substantially elevated in endurance athletes after running but does not correlate with cardiac function, other biomarkers, or myocardial fibrosis. In mice, we demonstrate that galectin-3 increase during endurance exercise originates primarily from skeletal muscle.